Association of composite dietary antioxidant index with high risk of prostate cancer in middle-aged and elderly men: insights from NHANES - Jin, Xuefeng; Tong, Wenhui; Sun, Li; Lu, Sujue; Sun, Pan; Li, Hangxu; Liu, Yan (Frontiers in Immunology, 2025)
ObjectivesIn the US, the most common type of cancer and the second leading cause of cancer-related death in men is prostate cancer (PCa). Food and lifestyle factors may influence the risk of developing prostate cancer. Therefore, research on dietary components associated with prostate cancer is essential for its prevention. Data from the National Health and Nutrition Examination Survey (NHANES) between 2003 and 2010 was used for this cross-sectional investigation involving 5,658 middle-aged and older American men.MethodsDietary antioxidant vitamins A, C, E, total carotenoids, zinc, and selenium were subtracted from the total mean, divided by the standard deviation, respectively, and then summed to become the CDAI. Participants were categorized as high risk for PCa if they had tPSA greater than 10 ng/mL or tPSA levels between 4 and 10 ng/mL with f/t PSA ratios of 25% or below; the remaining subjects were classified as being at low risk for PCa.ResultsThe sample represented approximately 75,984,602 American men. After multivariate logistic regression, dose-effect analysis and stratified analysis, CDAI was significantly and linearly negatively associated with a high risk of prostate cancer (OR=0.95, P=0.002, P for linear=0.0021). Age moderation analysis showed a significant effect on the inverse relationship between CDAI and prostate cancer risk (B = -0.0097, SE = 0.0034, t = -2.85, P = 0.004). Among the independent effects of CDAI components, zinc and selenium were more strongly negatively associated with prostate cancer (zinc, OR = 0.80, P = 0.008; selenium, OR = 0.78, P< 0.001).ConclusionsCDAI serves as a dietary indicator of prostate cancer risk in middle-aged and older men, and high dietary antioxidant intake has a significant protective effect on prostate cancer risk, especially in the older population of men.